Molecular Plant Breeding - Yunbi, Xu (CABI, 2014)
The genomics revolution of the past decade has greatly enhanced our understanding of the genetic composition of living organisms including many plant species of economic importance. Complete genomic sequences of Arabidopsisand several major crops, together with high-throughput technologies for analyses of transcripts, proteins and mutants, provide the basis for understanding the relationship between genes, proteins and phenotypes. Sequences and genes have been used to develop functional and biallelic markers, such as single nucleotide polymorphism (SNP), that are powerful tools for genetic mapping, germplasm evaluation and marker-assisted selection. The road from basic genomics research to impacts on routine breeding programmes has been long, windy and bumpy, not to mention scattered with wrong turns and unexpected blockades. As a result, genomics can be applied to plant breeding only when an integrated package becomes available that combines multiple components such as high-throughput techniques, cost-effective protocols, global integration of genetic and environmental factors and precise knowledge of quantitative trait inheritance. More recently, the end of the tunnel has come in sight, and the multinational corporations have ramped up their investments in and expectations from these technologies. The challenge now is to translate and integrate the new knowledge from genomics and molecular biology into appropriate tools and methodologies for public-sector plant breeding programmes, particularly those in lowincome countries. It is expected that harnessing the outputs of genomics research will be an important component in successfully addressing the challenge of doubling world food production by 2050.